Analisis Bauran Pemasaran dalam Meningkatkan Penjualan Produk Topi pada CV Stabil Distro - Rian Firmansyah; Angga Nadiyanto Prastian (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the implementation of the marketing mix strategy (7P marketing mix) implemented by CV Stabil Distro in an effort to increase sales of hat products. The approach used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The research subjects consisted of the business owner, marketing staff, and several consumers who have made purchases. The focus of this study lies in how each element in the 7P marketing mix, namely product, price, place, promotion, people, process, and physical evidence, is implemented by the company, and how it influences consumer purchasing decisions. The results show that the elements of product, promotion, and process are the most dominant factors in attracting consumer buying interest. CV Stabil Distro utilizes social media such as Instagram and WhatsApp, as well as marketplaces like Shopee to reach a wider market. In addition to digital promotions, offline promotions are also carried out to increase brand visibility. However, the company faces several obstacles such as intense price competition, rapidly changing fashion trends, and obstacles in the distribution process. As a solution, this study recommends product diversification strategies, improving delivery service quality, and collaborating with influencers to enhance competitiveness. These findings are expected to not only contribute theoretically to the literature on marketing strategies in the local fashion sector but also serve as a practical reference for MSMEs in formulating marketing strategies that adapt to market dynamics.